Mothers’ and Fathers’ Science-Related Talk With Daughters and Sons While Reading Life and Physical Science Books - Shirefley, Tess A.; Leaper, Campbell (Frontiers in Psychology, 2022)
Introduction: In prior studies conducted in the U.S., parents’ gender-differentiated encouragement of science predicted children’s later science motivation. Most of this work has focused on older children or teens and only looked at the impact of mothers. However, accumulating evidence suggests that gender-differentiated encouragement of science interest may begin in early childhood. Moreover, fathers may be more likely than mothers to treat boys and girls differently in science-learning contexts. Methods: We examined 50 U.S. families with both a mother and a father (82% White; 98% with at least some college education) and either a daughter or a son (48 to 83 months; M=62, SD=9). On separate visits, each parent read two books with their child. One was about life science and the other was about physical science. We coded parents’ science-related talk during these interactions. Results and Conclusions: Contrary to our predictions, parents used higher proportions of science talk with daughters than sons—including higher average rates of overall science talk and specific types of science talk (science explanations, science-related personal connections, and science-learning talk). Moreover, most of the child gender effects occurred while reading the physical science books. Book topic and parent gender moderated some additional patterns. Book reading is discussed as a potential context for mitigating socialization experiences that traditionally disfavor girls’ interest in physical science. Keywords: Gender Differences; Mother Child Communication; Father Child Communication; Reading; Science Education